2005
DOI: 10.1002/apj.5500130329
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Submicron and Residual Ash Particle Formation during Pulverised Coal Combustion: A Comprehensive Review

Abstract: Coaljly ash has been a traditional concern of utilities since coal was used to generate electricity because it may bring about a number of technical and economic problems

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In combustion systems, the very fine particles (especially the submicron aerosols) could readily escape conventional air pollution control devices (APCDs) and thus might pose serious risks to human health [4]. The health concerns have stimulated extensive research [7][8][9][10][11][12] on ash aerosol formation and properties in the last decades. Such information is of great significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In combustion systems, the very fine particles (especially the submicron aerosols) could readily escape conventional air pollution control devices (APCDs) and thus might pose serious risks to human health [4]. The health concerns have stimulated extensive research [7][8][9][10][11][12] on ash aerosol formation and properties in the last decades. Such information is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…A number of related reviews are available in books [8,10,[13][14][15][16], academic journals [7,9,11,12,17], and conference proceedings [18,19]. However, most of them only discussed ash aerosols from pulverized coal combustion (PCC).…”
Section: Introductionmentioning
confidence: 99%
“…It could range from sizes greater than 30 microns to submicron. 28 Smaller, submicron slag droplets are formed predominantly due to vaporization and consequent condensation of metal oxides. 29 Larger slag droplets are formed as a result of complete coalescence.…”
Section: C 2015 American Institute Of Chemical Engineersmentioning
confidence: 99%
“…In this scenario, all the mineral content in the char particle coalesce to form a single slag droplet. 27,28 Given the extreme conditions within the gasifier, it is not necessary that the agglomerated mineral matter will only detach from the char particle when it approaches complete burnout. It is found that the separation of individual included mineral matter or partially coalesced mineral inclusion is found to result in sizes between 1 and 20 microns due to shedding or char fragmentation.…”
Section: C 2015 American Institute Of Chemical Engineersmentioning
confidence: 99%
“…Examples of such time-varied aerosols are the nucleation event of particles in the atmosphere (Weber et al, 1995(Weber et al, , 1996Mäkelä et al, 1997;Kulmala, 2003Kulmala, , 2004Kulmala, , 2013 and the aerosols produced by the combustion processes (Flagan, 1979;Leskinen et al, 1998;Yu et al, 2005;Xu et al, 2011). The performance of aerosol instruments under the challenge of time-varied aerosols needs to be understood in order to properly characterize the transient behavior of aerosols.…”
Section: Introductionmentioning
confidence: 99%